Penerapan Model Nature Learning Dalam Kemampuan Menulis Teks Puisi Pada Siswa Kelas VIII MTSN 4 Karawang - Kurniawan, Andhika Putra; Syafroni, Roni Nugraha; Rosalina, Sinta (Peneliti.net, 2024)
This study aims to determine the application of the Nature Learning model in the ability to write poetry texts in class VIII students at MTsN 4 Karawang. In this learning context, students need to understand the elements involved in composing poetry. This research attempts to apply the Nature Learning learning model in learning to write poetry for Grade VIII students at MTsN 4 Karawang. This research method is a quantitative research with a quasi-experimental design. The population of this study were all students of class VIII at MTsN 4 Karawang, and the sample was selected using a random sampling method, with two classes selected: class VIII A as the control group and class VIII C as the experimental group. Data was collected through a poetry writing test. The validity of the instrument was tested using construct validity by consulting experts and trials on students who had studied pantun material at Rengasdengklok 2 Public Middle School. Data were analyzed using the t-test with a significance level of 5%, after ensuring that the data prerequisites were met (normality test, homogeneity test, and N-gain test using SPSS version 26). The results of data analysis showed that both groups had normal data distribution (significance value > 0.05) and data homogeneity (values > 0.05 for pretext and posttest homogeneity). This study found a significant difference between the control and experimental groups with a significance level of 0.001 <0.05. The Nature Learning learning model has an average N-gain value of 56.17%, indicating a sufficient level of effectiveness in learning to write poetry. The final results of this study indicate that the application of the Nature Learning learning model has a significant difference from the application of conventional models.